Impedimetric non-enzymatic glucose sensor based on nickel hydroxide thin film onto gold electrode - Rinaldi, Ana Laura (2016)
A non-enzymatic glucose sensor based on a thin layer of nickel immobilized on a gold electrode (EAuNi(OH)2) was used to perform impedimetric determination of glucose. The electrodeposition solution, composed of 0.010 M Ni(NO3)2·6H2O and 1 M of chloride, allows only one active catalyst (NiOOH) to be present on the gold electrode surface after activation with 0.1 M KOH. Electrochemical oxidation of glucose on EAuNi(OH)2 electrode was evaluated by Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS) in the concentration range of 0-14.8 mM of analyte. Ip/v1/2 vs scan rate graph shows a typical catalytic behavior by EAuNi(OH)2 toward glucose oxidation. Measurements in the presence of possible interfering species (ascorbic acid, uric acid, dopamine) did not affect the response of the analyte of interest. EIS offers good sensibility and selectivity for the glucose detection by non-enzymatic glucose sensor as an alternative to conventional methods. A single-frequency impedance method is proposed as transduction principle. For that, the parameters of complex impedance (module, phase, real and imaginary impedance) at each frequency were evaluated in function of glucose concentration and in terms of correlation coefficient. These analyses show a better linear response for the module of impedance (|Z|) in the range of 0-2 mM of glucose at 0.1 Hz (R2 = 0.984) with a slope of 484.7 Ω mM-1 of glucose. Finally, EAuNi(OH)2 was successfully applied to the assay of glucose in blood samples.